Cardiovascular responses to low-intensity isometric handgrip exercise in coronary artery disease: effects of posture - Gois, Mariana de Oliveira; Simões, Rodrigo Polaquini; Porta, Alberto; Kunz, Vandeni Clarice; Pastre, Carlos Marcelo [UNESP]; Catai, Aparecida Maria (Elsevier, 2019)
Background: Coronary artery disease (CAD) lead to cardiovascular autonomic control disfunctions that can worsen exercise and/or posture adjustments. Objectives: To verify the cardiovascular responses to low-intensity isometric handgrip exercise performed in different postures in CAD patients. This study tested the hypothesis that the posture influences the cardiovascular responses during isometric handgrip exercise and that the presence of CAD promotes greater cardiovascular stress during this type of exercise. Methods: We investigated cardiovascular responses to isometric handgrip exercise in 15 CAD patients (CADG) and 15 health matched-control (CG). The subjects performed isometric handgrip exercise at 30% of maximum voluntary contraction until exhaustion in SUPINE, SITTING and STANDING positions. Systolic arterial pressure, diastolic arterial pressure, mean blood pressure, heart rate, peripheral vascular resistance, cardiac output, stroke volume and double product were measured during rest (baseline), exercise (peak value) and recovery in the 1st minute (REC1). Delta PB (ΔPB, peak minus baseline) and PR1 (ΔPR1, peak minus REC1) were calculated. Results: Higher ΔPB and ΔPR1 of systolic and mean arterial pressure and double product were observed in STANDING when compared to SITTING and/or SUPINE. CADG showed higher ΔPB of systolic and mean arterial pressure in all postures and higher ΔPR1 of strove volume in the SITTING. Conclusion: We concluded that the posture during isometric handgrip exercise influences the cardiovascular responses with STANDING leading to higher cardiovascular stress. CAD promoted higher arterial pressure responses however these responses were physiological and expected due to the presence of disease and type of exercise.
Keywords: Blood pressure; Cardiovascular system; Heart rate; Isometric contraction; Physical therapy; Postures